1989
DOI: 10.1002/aic.690351219
|View full text |Cite
|
Sign up to set email alerts
|

Effects of raffinose on sucrose crystal growth kinetics and rate dispersion

Abstract: Raffinose is a major impurity in sugar production from sugar beets. It exists to the extent of 0.3 to 1.2% of the sugar present in the beet (McGinnis, 1971). Previous research (Smythe, 1967b Mantovani and Fagioli, 1964;Binder and Murphy, 1982;Vaccari et al., 1986) has shown that raffinose has a strong effect on both the habit and the growth rate of sucrose crystals grown in its presence. Powers (1960). Hungerford and Nees (l934), Smythe ( 1967a), and Vaccari et al.(1 986) among others have shown that raffinos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Because of its chemical structure and orientation, raffinose was not only adsorbed onto the surface, it was physically incorporated into the sucrose crystal. The accompanying galactose created a steric hindrance, which stopped further growth on that face of the sucrose crystal (Liang et al. , 1989).…”
Section: Resultsmentioning
confidence: 99%
“…Because of its chemical structure and orientation, raffinose was not only adsorbed onto the surface, it was physically incorporated into the sucrose crystal. The accompanying galactose created a steric hindrance, which stopped further growth on that face of the sucrose crystal (Liang et al. , 1989).…”
Section: Resultsmentioning
confidence: 99%
“…This value is typical for the crystallization of simple sugars. Previous research on crystal growth of sucrose for example, gives an activation energy of crystal growth as 28.9 to 33.1 kJ/mol for growth from pure solutions, and 45.6 to 57.7 kJ/mol for growth from solutions having raffinose as an impurity.
9 Mean size crystal growth rates for α-glucose monohydrate as a function of relative supersaturation at 10 (·), 25 (▪), and 40 °C (◆).
10 An Arrhenius plot of the growth rate constant for determination of the activation energy of crystal growth.
…”
Section: Resultsmentioning
confidence: 99%
“…This value is typical for the crystallization of simple sugars. Previous research on crystal growth of sucrose 22 for example, gives an activation energy of crystal growth as 28.9 to 33.1 kJ/mol for growth from pure solutions, and 45.6 to 57.7 kJ/mol for growth from solutions having raffinose as an impurity.…”
Section: Effect Of Observation Time and Temperature On Sntmentioning
confidence: 99%
“…A large number of experiments, including early work in growth cells by the group of Berglund, have shown that individual crystals within a population grow at a constant rate over time if the solution conditions remain constant; these results preclude the mechanism of size-dependent growth since the size of the crystals does change significantly over the time of the experiment, whereas the growth rate is constant. However, the individuals within the population (under the same conditions) do not all grow at the same rate; there is a distribution of growth rates within the population.…”
Section: Results and Discussionmentioning
confidence: 99%